2007
DOI: 10.1007/s10661-007-9972-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole body vibration exposure in heavy earth moving machinery operators of metalliferrous mines

Abstract: As mining operations get mechanized, the rate of profit generation increases and so do the rate of occupational hazards. This study deals with one such hazard - occupational vibration. The present study was carried out to determine the whole body vibration (WBV) exposure of the heavy earth moving machinery (HEMM) operators in two types of metalliferous mines in India, when they were engaged in the mining activity. Cross-comparison was done of the vibration dose value (VDV) for HEMM operators as well as each ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…The impact of vibration on physical and technical capacity of the drivers may be related to the exposure time, intensity and frequency, as well as the operational and environmental conditions in which the activity is developed (11,15). Evidence suggests that WBV exposure time triggers micro and macro impacts in the spine, and presents a clear relationship between the driver's position and the impact of transmission to important areas in the musculoskeletal system that directly compromises the absorption and dissipation of forces (11, 16 -18).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of vibration on physical and technical capacity of the drivers may be related to the exposure time, intensity and frequency, as well as the operational and environmental conditions in which the activity is developed (11,15). Evidence suggests that WBV exposure time triggers micro and macro impacts in the spine, and presents a clear relationship between the driver's position and the impact of transmission to important areas in the musculoskeletal system that directly compromises the absorption and dissipation of forces (11, 16 -18).…”
Section: Introductionmentioning
confidence: 99%
“…The vibration suffered by workers when operating with vehicles depend on, among others, the external excitation force, the mass of the vehicle and environmental factors such as the condition of the pavement, the characteristics of the material handled, operations organization and worker experience (Mandal & Srivastava 2010;Frimpong, Galecki et al 2011). As expected, exposure to WBV does not depend on the type of operation (raw material), but from the working conditions and the type of equipment used as stated by the authors as Vanerkar, Kulkarni et al (2008).…”
Section: Methodologies Applied To the Measurement Of Vibrations Transmentioning
confidence: 65%
“…Some studies point to WBV values below 0.5 m.s -2 (Howard, Sesek et al 2009;Aye & Heyns 2011;Dentoni & Massacci 2013). However, authors like Vanerkar, Kulkarni et al (2008) call attention to the risk conditions that may be subject these workers, with WBV values reaching 2.3 m.s -2 . The same happens with the predominant axis, there is no a clear definition.…”
Section: Shovelsmentioning
confidence: 99%
“…A number of individual characteristics, such as age and smoking [7], height and weight [8] and mental stress [9], have also been associated with musculoskeletal symptoms. Operators of vehicles used in mining operations are exposed to considerable WBV during relatively long work periods [10][11][12][13][14][15]. Studies have also shown that the prevalence of self-reported musculoskeletal symptoms is higher among drivers of mine vehicles than among nonexposed workers [16,17].…”
Section: Introductionmentioning
confidence: 99%